EXPLORES THE INTEGRATION OF TECHNOLOGY INTO LANGUAGE LEARNING IN THE CONTEXT OF ENGLISH AS A SECOND LANGUAGE IN PEDAGOGICAL UNIVERSITIES - Orasta Hamraqulova (European Science Publishing, 2024)
Language learning has transformed the way languages are learned and taught since the advent of technologies and the development of digital world. However, the role of technologies should be clarified when they are used as a medium of instruction or as a teaching tool. This paper investigates the incorporation of technologies into language learning in a context of English as a second language. The research subjects are students of a private university who study the language for vocational purposes. The study uses quasi-experimental method as the research subjects are selected among students of the researcher.
Keywords: digitalization, cognitive skills, cognitive tools, cognitive performance, conventional methods, critical thinking.